By word of mouse: using animal models in venous thrombosis research. (18th May 2020) - Campos, Joana; Brill, Alexander
Abstract: Deep vein thrombosis (DVT) is a disease with high prevalence and morbidity. It can lead to pulmonary embolism with severe respiratory insufficiency and risk of death. Mechanisms behind all stages of DVT, such as thrombosis commencement, propagation, and resolution, remain incompletely understood. Animal models represent an invaluable tool to explore these problems and identify new targets for DVT prevention and treatment. In this review, we discuss existing models of venous thrombosis, their advantages and disadvantages, and applicability to studying different aspects of DVT pathophysiology. We also speculate about requirements for an "ideal model" that would best recapitulate features of human DVT and discuss readouts of various models.